HORMONAL AND ENERGETIC CHANGES IN PATIENTS WITH ENDOMETRIAL HYPERPLASIA AND ENDOMETRIAL CANCER - A. L. Chernyshova; L. A. Kolomiets; N. V. Yunusova; Е. V. Shanshashvili (Сибирский онкологический журнал, 2016)
Hormonal and energetic status was studied in 168 patients with endometrial hyperplasia and endometrial cancer. The comparative analysis of hormonal status (LH, FSH, estrogen, progesterone, testosterone, prolactin, SHBG), energetic status (leptin, grelin, insulin) and the assessment of lipid and carbohydrate metabolisms were carried out for patients with proliferative processes in the endometrium with the evidence of metabolic syndrome and without it. The study showed that the changes in hormonal status were characterized by a high frequency of disturbances with development of hyperestrogenemia (72 %), hypertestosteronemia (65 %), hyperinsulinemia (81 %) and hyperleptinemia (68 %). Moreover, the LH level and LH/FSH index were increased and FSH and progerterone levels were decreased. Significant changes in both carbohydrate (hyperinsulinemia, insulin resistance) and lipid (hypercholesterolemia, hypertriglyceridemia) metabolisms were revealed. The mechanisms of hormonal correlations that underlie pathological endometrial process were described.